Implementation of CDK4/6 Inhibitors and its Influence on the Treatment Landscape of Advanced Breast Cancer Patients – Data from the Real-World Registry PRAEGNANT - Engler, Tobias; Fasching, Peter A.; Lüftner, Diana; Hartkopf, Andreas D.; Müller, Volkmar; Kolberg, Hans-Christian; Hadji, Peyman; Tesch, Hans; Häberle, Lothar; Ettl, Johannes; Wallwiener, Markus; Beckmann, Matthias W.; Hein, Alexander; Belleville, Erik; Uhrig, Sabrina; Wimberger, Pauline; Hielscher, Carsten; Kurbacher, Christian M.; Wuerstlein, Rachel; Untch, Michael; Taran, Florin-Andrei; Enzinger, Hans-Martin; Krabisch, Petra; Welslau, Manfred; Maasberg, Michael; Hempel, Dirk; Lux, Michael P.; Michel, Laura L.; Janni, Wolfgang; Wallwiener, Diethelm; Brucker, Sara Y.; Fehm, Tanja N.; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2022)
Background Comprehensive data from prospective clinical trials have led to a high level of evidence establishing CDK4/6 inhibitors in combination with endocrine treatment (CDK4/6i + ET) as a standard for the treatment of HER2-negative, hormone receptor-positive (HER2− HR+) breast cancer patients in the first-line advanced therapy setting. Data on patient populations that have been treated in the real-world setting may provide an insight into changes of patient characteristics and prognosis over time.Methods The data were extracted from the prospective real-world registry PRAEGNANT (NCT02338167). Patients had to have HER2− HR+ advanced breast cancer in the first-line metastatic setting. The chosen therapies were described as well as progression-free survival (PFS) and overall survival (OS) in relation to the given therapies and time periods during which they were indicated.Results CDK4/6 inhibitors have been rapidly implemented since their introduction in November 2016. In recent years (2018 – 2022), about 70 – 80% of the patient population have been treated with CDK4/6 inhibitors, while endocrine monotherapy was given to about 10% and chemotherapy to about 15% of all patients. The prognosis was worst in patients treated with chemotherapy. Recently, mainly patients with a good prognosis are being treated with endocrine monotherapy, and patients who are treated with chemotherapy have an unfavorable prognosis. The PFS and OS of patients treated with CDK4/6i + ET have remained similar over time despite changes in patient characteristics.Conclusion A treatment with CDK4/6i + ET has rapidly become the therapy standard for patients in the first-line advanced breast cancer setting. After the implementation of CDK4/6i + ET, endocrine monotherapy is only given to patients with a very favorable prognosis, while chemotherapy is provided to patients with a rather unfavorable prognosis. These changes in patient characteristics did not seem to influence the prognosis of patients treated with CDK4/6i + ET.
Keywords: advanced breast cancer; real world data; chemotherapy; CDK4/6 inhibitor; endocrine treatment